Statistical properties of dynamical chaos - Vadim S. Anishchenko; Tatjana E. Vadivasova; Galina I. Strelkova; George A. Okrokvertskhov (Mathematical Biosciences and Engineering)
This study presents a survey of the results obtained by the authors on statistical description of dynamical chaos and the effect of noise ondynamical regimes. We deal with nearly hyperbolic and nonhyperbolic chaoticattractors and discuss methods of diagnosing the type of an attractor. Weconsider regularities of the relaxation to an invariant probability measure fordifferent types of attractors. We explore peculiarities of autocorrelation decay and of power spectrum shape and their interconnection with Lyapunovexponents, instantaneous phase diffusion and the intensity of external noise.Numeric results are compared with experimental data.